Natural disasters, epidemics and intergovernmental relations : more or less decentralisation? - Mello, Luiz de (2022)
The subnational governments, at the regional and local levels, play an important role in the prevention, management and recovery from natural disasters and pandemics/epidemics. These jurisdictions are responsible for issuing and monitoring compliance with several aspects of regulation that are essential for risk prevention, including land use and construction codes; for providing frontline services that are crucial for effective crisis management, including health care, civil protection, and public order and safety; and for rebuilding lost or damaged physical infrastructure in the recovery phase. This paper provides empirical evidence based on impulse response functions that the occurrence of natural disasters and the outbreak of pandemics/epidemics are associated with an increase in the subnational shares of government spending and revenue in the years following these shocks. These decentralisation effects vary according to specific shocks and are conditional on the business cycle: they tend to be stronger when the shocks materialise during cyclical expansions